Factor Structure of the Bulgarian Version of FOCUS on the Outcomes of Communication Under Six - Stankova, Margarita; Djalev, Lubomir; Kamenski, Tsveta; Mihova, Polina (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
The aim of this paper is to present the Factor structure of the Bulgarian version of FOCUS on the Outcomes of Communication Under Six. The instrument is based on the World Health Organisation’s (WHO) International Classification of Functioning, Disability and Health – Children and Youth (ICF-CY), and it aims at tracing the effect of therapy on the child’s communication and participation in the real world. Our research is focused on the factor structure and reliability of the Parent’s form. The participants formed two samples, the main one consisting of 272 (mostly preschool children), males and females. The age of the subjects varied between 2.17 and 7.25 years, with a mean age of M = 4.91 years and SD = 1.10. The latent structure of the questionnaire was examined in five phases – 1-test of the assumption of one-dimensionality; 2-exploratory factor analysis was applied to establish the factor model, based on data from an empirical study; 3-three possible factor models with a fixed number of factors were analyzed; 4-the factor models were compared through confirmatory factor analysis. The aim of the analyses was to select the most appropriate final model for the Bulgarian version of the questionnaire. The reliability analysis of the scales in the two-factor model was conducted through testing their internal consistency. The two-factor model of the FOCUS questionnaire in Bulgarian shows a good orientation towards two specific functions – ‘capacity for communication’, and ‘performance’ or ‘communicative performance’. Due to its stable measurements related to functioning, this tool could be effectively used to practically assess the effect of therapy on children with development disorders.